AVOCADO STOCK PREDICTION SYSTEM IN FRUIT SHOPS: A Case Study in Bantul City - Setiawan, Wisnu; Hastono, Tri; Gunawan, Riyan Fahmi (JTH: Journal of Technology and Health, 2023)
This study aims to develop a predictive system for avocado stock that can be used by fruit stores in Bantul City. This case study was conducted to analyze and predictavocado inventory based on historical data and other factors influencing demand and supply in the area. The method used in this research is the prediction method using Adaline (Adaptive Linear Neuron). The results show that this avocado stock prediction system can assist fruit stores in optimizing inventory and avoiding stockouts. The implementation of this system is expected to enhance efficiency andcustomer satisfaction in fruit stores in Bantul City. Further research is recommended to conduct a more in-depth analysis of the factors influencingavocado demand and supply in Bantul City to improve stock predictionaccuracy. Keywords: predictive system, avocado stock, fruit store, inventory management, Bantul City.